Fake News and Libraries: How Teaching Faculty in Higher Education View Librarians’ Roles in Counteracting the Spread of False Information - Alwan, Ahmed; Garcia, Eric P.; Kirakosian, Antranik T.; Weiss, Andrew P. (Partnership, 2021)
This paper reports on a survey of faculty members at California State University, Northridge (CSUN) in Los Angeles, California, regarding their attitudes about libraries’ and librarians’ roles in the area of fake news. This study is a continuation of a previous paper that reviewed the origins of fake news and faculty perceptions of the concept. The survey results suggest that faculty members have differing views of how libraries and librarians can help them address fake news. Across disciplines, ages, and genders, faculty members’ views show little belief in the use of the library or librarians to help combat fake news. Notably, only lecturers seem to have a strong view of libraries and librarians playing helpful roles in dealing with the fake news phenomenon. These findings may have future implications for librarians who attempt to address fake news with either their faculty or their students. It may be necessary to develop broader outreach and awareness programs to change traditional conceptions of academic librarians and library services, which are often conflated.